Pengaruh Metode Analisis Tugas Dalam Meningkatkan Kemampuan Diri Sendiri Pada Anak Tuna Grahita Sedang di SLB Kembar Karya Pembangunan 3 Bekasi - Widijastuti (Program Studi Akuntansi IKOPIN, 2022)
This research aims to improve the ability to take care of yourself by using the task analysis method at SLB Kembar Karya Pembangunan 3. The research was carried out at the SLB Kembar Karya Pembangunan 3. The subjects studied were SDLB grade 3 students. This study used a task analysis method with an action intervention pattern, namely taking steps that were carried out in cycles, and the technique used in this action research was triangulation with data in the form of observation sheets. , while qualitative data and for the percentage used quantitative data. The results of the research show that self-development learning activities. Especially in brushing teeth in class II moderate intellectual impairment using the task analysis method proved successful with the ability level to achieve mastery above 60% in each cycle.